The voice of dual status - Akerman, Geraldine (Sexual crime, 2024)
Much research has examined the personal histories of those who have committed sexual offences with the aim of uncovering events and factors that may influence and in part explain the development of a tendency and propensity to commit a sexual offence. One of the most frequently discussed explathir of sexual offending is the experience of sexual abuse in childhood. Throughout the chapter we will illustrate the theory, with quotes (in italics) from two residents in therapy at HMP Grendon, who have experienced sexual abuse and perpetrated sexual violence. This approach was taken because there is a dearth of research in which the voice of those who have experienced in this area, and would otherwise be just a statistic, is heard. The chapter starts with an overview of research considering those who have experienced Adverse Childhood Experiences (ACE) and the links to offending behaviour. The chapter then moves specifically to look at the research surrounding those who have been sexually abused and go onto to commit sexual offences. The second part of this chapter explores the evidence surrounding therapeutic communities as a treatment approach for those who have committed sexual offences. Throughout the chapter the resident authors (pen names given for anonymity) have shared their experiences.